Complete genome, catabolic sub-proteomes and key-metabolites of Desulfobacula toluolica Tol2, a marine, aromatic compound-degrading, sulfate-reducing bacterium - Wöhlbrand, Lars; Jacob, Jacob H.; Kube, Michael; Mussmann, Marc; Jarling, René; Beck, Alfred; Amann, Rudolf; Wilkes, Heinz; Reinhardt, Richard; Rabus, Ralf (Environmental microbiology, 2013)
Summary Among the dominant deltaproteobacterial sulfate‐reducing bacteria (SRB), members of the genus Desulfobacula are not only present in (hydrocarbon‐rich) marine sediments, but occur also frequently in the anoxic water bodies encountered in marine upwelling areas. Here, we present the 5.2 Mbp genome of Desulfobacula toluolica Tol2, which is the first of an aromatic compound‐degrading, marine SRB. The genome has apparently been shaped by viral attacks (e.g. CRISPRs) and its high plasticity is reflected by 163 detected genes related to transposases and integrases, a total of 494 paralogous genes and 24 group II introns. Prediction of the catabolic network of strain Tol2 was refined by differential proteome and metabolite analysis of substrate‐adapted cells. Toluene and p‐cresol are degraded by separate suites of specific enzymes for initial arylsuccinate formation via addition to fumarate (p‐cresol‐specific enzyme HbsA represents a new phylogenetic branch) as well as for subsequent modified β‐oxidation of arylsuccinates to the central intermediate benzoyl‐CoA. Proteogenomic evidence suggests specific electron transfer (EtfAB) and membrane proteins to channel electrons from dehydrogenation of both arylsuccinates directly to the membrane redox pool. In contrast to the known anaerobic degradation pathways in other bacteria, strain Tol2 deaminates phenylalanine non‐oxidatively to cinnamate by phenylalanine ammonia‐lyase and subsequently forms phenylacetate (both metabolites identified in 13C‐labelling experiments). Benzoate degradation involves CoA activation, reductive dearomatization by a class II benzoyl‐CoA reductase and hydrolytic ring cleavage as found in the obligate anaerobe Geobacter metallireducens GS‐15. The catabolic sub‐proteomes displayed high substrate specificity, reflecting the genomically predicted complex and fine‐tuned regulatory network of strain Tol2. Despite the genetic equipment for a TCA cycle, proteomic evidence supports complete oxidation of acetyl‐CoA to CO2 via the Wood‐Ljungdahl pathway. Strain Tol2 possesses transmembrane redox complexes similar to that of other Desulfobacteraceae members. The multiple heterodisulfide reductase‐like proteins (more than described for Desulfobacterium autotrophicum HRM2) may constitute a multifaceted cytoplasmic electron transfer network.